Technical and economic feasibility analysis of solar power plant design with off grid system for remote area MSME in Semarang City. Issue 1 (November 2021) - Windarta, J; Handoko, S; Sukmadi, T; Irfani, K N; Masfuha, S M; Itsnareno, C H
Abstract: The distribution of electricity from State Electricity Enterprise does not necessarily reach remote areas, so these areas require alternative sources of electricity, such as solar power plants. This study aims to design and analyze the potential of small-scale off-grid PV in terms of engineering and economics. The research method has used a simulation on PVSyst software with four components, namely solar panels and batteries. The research results were obtained based on four variations made: a 700Wp panel, a 24V 150Ah battery, and an 800W inverter. The design will produce electrical energy of 2 kWh/kWp/day with a total investment value of IDR 54, 268, 068 for a project period of 24 years. Compared to using a one kVA generator, the investment value was approximately IDR 208, 575, 063 for a 24-year project. Compared to batteries with the same specifications using a State Electricity Enterprise electricity charging source, the investment value for a 24-year project was IDR 81, 036, 162. NPV values in all variations obtained < 0, and PBP > the system project period. Thus, this system was considered not economically feasible and did not provide profit. Still, the off-grid solar power plant option was the most profitable than generators or battery power sources with State Electricity Enterprise charging.